Accumulation of metals in the gills of tilapia fingerlings (Oreochromis niloticus) from in vitro toxicology study - Yunus, Kamaruzzaman; John, Akbar; Khan Chowdhury, Ahmed Jalal; Saad, Shahbudin (Academic Journals, 2010)
A laboratory experiment was conducted to determine the different level of accumulation of zinc (Zn), copper (Cu) and lead (Pb) in 21 days fingerlings tilapia (Oreochromis niloticus). The concentration of these metals in the gills was detected through Inductively-Coupled Plasma Mass Spectrometer (ICP-MS). It was observed that the tilapia fingerlings can accumulate up to 3000 ppb of Zn after 21 days of exposure. The accumulation rate of Cu at 7 to 14 days was between 0.01 to 0.02 μg kg-1 while steady increase (0.06 ppb) was detected when exposure period extended to next 7 days. Meanwhile, gradual increase in Zn accumulation was observed at all the time. The fish had accumulated up to 142 μg kg-1 of Pb at the highest concentration in 30 days of exposure proved that there is a elevated three fold increase in Pb uptake compared with first ten and 20 days of exposure. It was also proven from this study that fishes exposed to longer period with minimal concentration tend to accumulate less heavy metal in gills since the heavy metals are transported to other parts of the body.